Doing the Work—or Not: The Promise and Limitations of Diversity, Equity, and Inclusion in US Medical Schools and Academic Medical Centers - Esparza, Caitlin Jade; Simon, Mark; Bath, Eraka; Ko, Michelle (Frontiers in Public Health, 2022)
While the number of positions, committees, and projects described as “Diversity, Equity, and Inclusion (DEI)” work has grown rapidly in recent years, there has been little attention to the theory, praxis, or lived experience of this work. In this perspective, we briefly summarize the research and concepts put forth by DEI leaders in higher education more broadly, followed by an analysis of the literature’s application to academic medicine. We then discuss the ways in which language obscures the nature of DEI and the necessity of scholarship to evaluate the extensive range of practices, policies, statements, and programs the label is given to.